Implementation of Tutoring Services for Elementary School Students - Subhan, Subhan (Council: Education Journal of Social Studies, 2025)
This study aims to describe the implementation and obstacles to the implementation of tutoring services in class IV Negeri 58 Tambana. This research method uses a qualitative approach with the subject of research being class IV teachers. The research instruments used were interviews, documentation, observation, field notes and questionnaires. The steps of data analysis include data reduction, data presentation, and verification. The results of the study indicate that teachers have not created a tutoring service program. Tutoring services are implemented by teachers according to their understanding. Tutoring services by teachers are understood as a form of assistance for students to achieve learning outcomes according to the set targets. In implementing tutoring services, teachers experience obstacles including limited understanding, time, and skills